SHARIA BANKING HUMAN RESOURCES DEVELOPMENT STRATEGY IN THE ERA OF INDUSTRIAL REVOLUTION 4.0 TOWARDS SOCIETY 5.0 - Insulinde Yuliyati; Rizka Maulida (INKLUSIF (JURNAL PENGKAJIAN PENELITIAN SYARIAH DAN ILMU HUKUM), 2023)
In the midst of increasingly disruptive globalization, humans are required to always maximize their potential in order to survive in global competition. So in this case Islam as a civilization ideology is considered to be a guideline for preparing human resources that are able to compete in the era of the Industrial Revolution 4.0 and Society 5.0. In this article, the author wants to focus on sharia banking and digital transformation as well as increasing the competitiveness of human resources in the era of the Industrial Revolution 4.0 and Society 5.0. The aim of this research is to describe, analyze and examine sharia banking HR development strategies in facing challenges in the era of disruption 4.0 towards civil society 5.0. The method used by the author is a qualitative descriptive method with a literature study approach technique. The results of this research are the role and strategy of sharia banking human resources that change the challenges of the industrial revolution 4.0 into an opportunity to realize civil society 5.0. The role and strategy of sharia banking to face the era of industrial revolution 4.0 and society 5.0, namely, firstly quality human resources, secondly digital transformation, thirdly banking products needed by society in facing the era of industrial revolution 4.0 and society 5.0.Keywords: Sharia Banking HR; Digital Transformation; Industrial Revolution 4.0; Â Society 5.0